Fuzzy Parametric Geometric Programming in Process Reliability Based on Fuzzy EPQ Model - B.S. Mahapatra, M.K.Mondal, M.B.Bera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper is developed under the influence of economic production quantity model with demand dependent unit production cost in fuzzy environment. Development of fuzzy cost coefficient and restriction on storage space has been done under the condition of flexibility and reliability in the production process. The inventory related costs and space parameters are treated as fuzzy numbers and solved by the fuzzy parametric geometric programming technique. The execution of sensitivity analyses caused by different measures performed here.